Struggling for new lives: Family and fertility policies in the Soviet Union and modern Russia - Ekaterina Selezneva (Institut für Ost- und Südosteuropaforschung (IOS), 2016)
During the 20th century, Russian women were assigned the triple role of social and political activists, workers, caregivers and mothers. This paper makes an overview of the main steps undertaken first by the Soviet and later by the modern Russian governments to influence family formation models and fertility levels, in order to improve the demographic situation over the period from 1917 until 2015. The overview pays close attention to such measures of demographic policy as marriage and divorce regulation, support of families through family benefits and the tax system, reconciliation of family and work spheres (maternity/paternity leaves, workplace flexibility measures), fertility promotion, childbearing and childcare support, as well as rare reproductive health protection initiatives.
Keywords: J12; J13; J18; P30; 330; fertility; Russia; family policy